Delineating the shallow‐marine stratigraphic traps of Lower‐Cretaceous incised valley sedimentation, Pakistan using post‐stack seismic colour inversion. (18th February 2021) - Naseer, Muhammad Tayyab
Abstract : Sub‐surface incised marine valleys form good reservoirs globally. Subsurface heterogeneities within thin‐bedded shallow‐marine sedimentary systems are complex developing petroleum plays during hydrocarbon exploration. A seismic colour inversion (SCI) tool is a useful component in seismic data analysis for predicting porous and hydrocarbon‐bearing reservoirs. In the present study, SCI was used for the demarcation of gas‐bearing stratigraphic sequences within the Indus Basin, SE Pakistan. The SCI better characterizes the gas‐bearing sand‐fills within the incised‐valley reservoir compared to the absolute average amplitude (AAA) derived from surface seismic data. The SCI tool enhances the structural configuration of numerous system tracts; including the lowstand system tract (LST) and transgressive systems tract (TST): phase shifts reveal 'sweet‐spots' within the faulted and sand‐filled incised valley. The gas‐bearing sand‐filled incised valley of the LST experiences phase reversals with SCI magnitudes of −5900 g/c.c.*m/s, which reflect the bright seismic responses for stratigraphic‐based reservoir characterization, and hence it may act as a direct hydrocarbon indicator (DHI). The TST, which proves to be the non‐reservoir segments of seal sediments, brightens the high‐acoustic impedance (A.I) SCI magnitudes of 5900 g/c.c.*m/s. Facies modelling discriminates the transgressive seal and regressive coarse‐grained sandstone‐filled incised valleys. A cross‐plot of SCI with net‐to‐gross (N/G) and porosity evidence remains an accurate thickness and porosity effects for sand‐filled incised valley reservoirs than compared to AAA. Abstract : Gas‐bearing incised‐valley sand‐fills of the lowstand system tract experience phase reversals with seismic coloured inversion (SCI) magnitudes of −5900 g/c.c.*m/s, which act as a direct hydrocarbon indicator (DHI). The transgressive system tract, which proves to be the non‐reservoir segments of seal sediments, brighten the high‐acoustic impedance (A.I) SCI magnitudes of 5900 g/c.c.*m/s.